A Descriptive Study of English Language Teaching for The Students of Faculty of Science and Mathematics and Faculty of Law - Jessica Setiawan; Istiqlaliah Nurul Hidayati; Atti Herawati (Pedagogia: Jurnal Ilmiah Pendidikan, 2015)
The English learned by university students is supposed to be different from faculty to faculty or from study program to study program. The aim of the research is to describe English Language Teaching process in the Faculty of Science and Mathematics and the Faculty of Law.There are two research questions in this study: 1) What materials do the lecturers teach to the students in Faculty of Science and Math and Faculty of Law? Is it General English (GE) or English for Specific Purposes (ESP)? 2) What method do the lecturers use in teaching English to the students in Faculty of Science and Math and Faculty of Law? In conducting this research, descriptive method is used to portray the phenomenon factually. The data were obtained through interview, observation, and documentation. The research was conducted to the first semester students of Pharmacy Study Program, Computer Sciences Study Program, and first semester students of Faculty of Law. Three English lecturers were taken as the participants. Triangulation was used to check the validity of the data. As the result, the writer found out from the result of the interview, observation and documentation that the materials taught in Faculty of Science and Mathematics and Faculty of Law was English for Specific Purposes (ESP). Discussion and lecturing were the methods applied by the English lecturer in Faculty of Law. Presentation and discussion were applied by the English lecturers in Pharmacy Study Program and Computer Sciences Study Program.